2020
DOI: 10.14715/cmb/2020.66.6.27
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol mediated regulation of deregulated signaling pathways in different cancers: Tumbling of the ninepins of molecular oncology

Abstract: With the recent technological advancements, a new golden era of natural products drug discovery has dawned. Increasingly it is being realized that structural modularity of many pharmacologically active products derived natural sources allows a building-block approach which can be exploited for analysis of regulation of deregulated oncogenic protein networks in different cancers. Piceatannol has been shown to effectively modulate JAK/STAT, Wnt/β-catenin, mTOR pathway in different cancers. In addition, certain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Therefore, some polyphenols with significant free radical scavenging activity, such as syringic acid, show neuroprotective activity ( Ogut et al, 2022a , Ogut et al, 2019 ). In addition to antioxidant activity, piceatannol also possesses apoptotic activity to cancer cell ( Nayyab et al, 2020 ). Previous study has indicated that these potent cytotoxic effects are accompanied by induction of DNA damage, increase of the proportion of cells in the sub-G(1) phase of cell cycle, and inhibition of reactive oxygen species (ROS) generation ( Jin et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some polyphenols with significant free radical scavenging activity, such as syringic acid, show neuroprotective activity ( Ogut et al, 2022a , Ogut et al, 2019 ). In addition to antioxidant activity, piceatannol also possesses apoptotic activity to cancer cell ( Nayyab et al, 2020 ). Previous study has indicated that these potent cytotoxic effects are accompanied by induction of DNA damage, increase of the proportion of cells in the sub-G(1) phase of cell cycle, and inhibition of reactive oxygen species (ROS) generation ( Jin et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, novel plant compounds with potential anti-cancer effects have been investigated in an increasing number of studies. Plant-derived natural products such as the phenolic compounds (Anantharaju et al 2016) (Nayyab et al 2020), alkaloids (Isah 2016) and terpenoids have recently gained interest due to the growing demand for discovering novel anti-cancer drug candidates (Tomko et al 2020) (Farooqi et al 2020). Molecular findings suggest that these natural products can act on major signaling mechanisms such as the JAK/STAT, Wnt/β-catenin, mTOR pathways and TRAIL-mediated apoptosis (Sun et al 2019).…”
Section: Introductionmentioning
confidence: 99%